(3JQJjH GdYdhes - (3SGLbdj RGOg , SGLbdj RGOg,J (B1150 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi YHGOg GdPjf GUWai GYdehG eYGTQ GdWdHI CMSf Gddg CehQge s
(3BNQgG (B:s
(3bO GMJhJ YdjgG cJH GdeJcdejf afMf ai TZd hZfi Yf eOGQSg YbGFO GdeTQcjf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B14s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B80 s
Keywords: (3GdeYGQa GdYGeIs